2021
DOI: 10.1124/dmd.121.000447
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into MAO B–Mediated Formation of CC112273, a Major Circulating Metabolite of Ozanimod, in Humans and Preclinical Species: Stereospecific Oxidative Deamination of (S)-Enantiomer of Indaneamine (RP101075) by MAO B

Abstract: Ozanimod, recently approved for treating relapsing MS, produced a disproportionate, active, MAO B-catalyzed metabolite (CC112273) that showed remarkable interspecies differences and led to challenges in safety testing. This study explored the kinetics of CC112273 formation from its precursor RP101075. Incubations with human liver mitochondrial fractions revealed K Mapp , V max and Cl int for CC112273 formation to be 4.8 M, 50.3 pmol/min/mg protein and 12 l/min/mg, respectively, while K M with human recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Previous research elucidated a species‐based difference of S1P5 selectivity of ozanimod, which shows reduced potency for mouse S1P5 resulting from a mutation of threonine to alanine at position 120 19 . Nonetheless, it was shown that mice are up to 11‐fold less efficient in generating the major ozanimod metabolite (CC112273) 48 . Therefore, ozanimod might require human metabolization for full receptor engagement 49,50 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research elucidated a species‐based difference of S1P5 selectivity of ozanimod, which shows reduced potency for mouse S1P5 resulting from a mutation of threonine to alanine at position 120 19 . Nonetheless, it was shown that mice are up to 11‐fold less efficient in generating the major ozanimod metabolite (CC112273) 48 . Therefore, ozanimod might require human metabolization for full receptor engagement 49,50 …”
Section: Discussionmentioning
confidence: 99%
“…19 Nonetheless, it was shown that mice are up to 11-fold less efficient in generating the major ozanimod metabolite (CC112273). 48 Therefore, ozanimod might require human metabolization for full receptor engagement. 49,50 In our study, we confirm that functional antagonism of S1P1 by ponesimod drives OPC differentiation, a key step in initiating (re)myelination, but does not affect axonal wrapping by OPCs in vitro.…”
Section: F I U R Ementioning
confidence: 99%
“…The metabolite was minimally observed in vitro due to sequential metabolism through P450 and MAO-B, and it had a much longer half-life (∼10 times that of ozanimod) in vivo . To make it more complex for development advancement, CC112273 was an active metabolite that had equal potency as ozanimod, making it the primary active drug related species in circulation that needed further characterization. , Bridging repeated-dose GLP PK studies in preclinical species had to be conducted to address the exposure and safety multiplier of disproportionate metabolites; additionally, the clinical PK-PD relationship and DDI potential had to be re-assessed before this new drug could gain approval.…”
Section: Unexpected Major Metabolites In Circulationmentioning
confidence: 99%